Leading corrections to the scaling function on the diagonal for the two-dimensional Ising model. (26th February 2019) - Forrester, P J; Perk, J H H; Trinh, A K; Witte, N S
Abstract: In the neighbourhood of the critical point, the correlation length of the spin–spin correlation function of the two-dimensional Ising model diverges. The correlation function permits a scaling limit in which the separation N between spins goes to infinity, but the scaling variable remains fixed, where t is the coupling, and t   =  1 the critical point. Previous work has specified these scaling functions (there is one for the critical point being approached from above, and another if approached from below) in terms of transcendents defined by a particular -form of the degenerate Painlevé V equation. For the diagonal–diagonal correlation, we characterise the first two leading large N correction terms to the scaling functions—these occur at orders N −1 and N −2 —in terms of solutions of a second order linear differential equation with coefficients given in terms of these transcendents, and show how they can be computed. We show that the order N −1 is trivial and can be eliminated through appropriate variables so that the leading non-trivial correction is of order N −2 . In this respect our solution is the first non-trivial correction to the scaling limit pair-correlation results given in the earlier literature, but restricted to the case with both spins on a diagonal.